Divided we stand? Professional consensus and political conflict in academic economics - Karl M. Beyer; Stephan Pühringer (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2019)
In this paper we address the issue of the role of ideology and political preferences of publically engaged economists and contribute to the debate on consensus in economics. To do so, we conduct a social network analysis on the signatories of economist petitions, which we identify as one channel for economists to exert public influence. We base our analysis on a sample of 77 public policy petitions and presidential anti-/endorsement letters from 2008-2017 in the United States with more than 6,400 signatories and check the robustness of our results with six sub-networks. Our contribution is twofold: On the one hand we provide an extended empirical basis for the debate on consensus in economics and the role of politics and ideology in economics. On the other hand we provide a viable tool to trace the ideological leaning of (prospective) economist petitions and economists based on the social structure of petition networks.
Keywords: 330; social network analysis; sociology of economics; consensus; public economists; economist petitions; United States